2019
DOI: 10.1177/1558866119838639
|View full text |Cite
|
Sign up to set email alerts
|

Current Priorities in Campus Recreation: A Multi-Institutional Study of Strategic Plans

Abstract: Strategic planning is a proactive process of analyzing an organization to identify the organization’s values, mission, vision, goals, and objectives. Within campus recreation, research has focused on the processes of strategic planning, without examining the distinct organizational strategies of individual departments. The purpose of the study was to examine the content and structure of strategic plans within campus recreation and identify major priorities across institutions as a means to inform campus recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The management of recreation facilities and programs has an impact on numerous stakeholders including the participants and employees. While diversity and inclusion is a goal often forwarded by collegiate recreation organizations and associations (Kaltenbaugh et al, 2017;Lower-Hoppe et al, 2019;Patchett & Foster, 2015), there is still critical work needed given ongoing research findings of inequitable experiences for recreation participants (Carter-Francique, 2011;Griffith et al, 2011;Schwartz & Corkery, 2011;Smith et al, 2007) and a lack of competency among recreation staff (Anderson et al, 2018;Kaltenbaugh et al, 2017).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of recreation facilities and programs has an impact on numerous stakeholders including the participants and employees. While diversity and inclusion is a goal often forwarded by collegiate recreation organizations and associations (Kaltenbaugh et al, 2017;Lower-Hoppe et al, 2019;Patchett & Foster, 2015), there is still critical work needed given ongoing research findings of inequitable experiences for recreation participants (Carter-Francique, 2011;Griffith et al, 2011;Schwartz & Corkery, 2011;Smith et al, 2007) and a lack of competency among recreation staff (Anderson et al, 2018;Kaltenbaugh et al, 2017).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…The importance of diversity and inclusion has been espoused in numerous ways and at numerous levels throughout the field. At the collegiate recreation department level, the valuing of diversity and inclusion has been articulated via organizational guiding principles such as missions, visions, values, and strategic plans as well as through staff trainings (Kaltenbaugh et al, 2017;Lower-Hoppe et al, 2019;Patchett & Foster, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Campus recreation, however, is more similar to community sport organizations than varsity athletics, as campus recreation prioritizes participation over competition. They are however also different in that campus recreation departments have their own or shared facilities, employ full-time staff, and dedicate resources to strategic planning (Haines, 2010; Lower-Hoppe et al, 2019). More generally, these findings underscore the importance of facilities, human resources and programs for sport organizations that prioritize participation.…”
Section: Discussionmentioning
confidence: 99%
“…Participation has also been found to improve when there are organized and structured programs for people to engage in (e.g., registered programs) (Borgers et al, 2016). Previous research has found that campus recreation departments prioritize having a diverse range of available programming (Lower-Hoppe et al, 2019) that can include intramurals, sport clubs, drop-in sports, outdoor recreation, group fitness, aquatics, instructional programming, special events and community activities (Stier et al, 2005). Stier et al (2005) highlighted that both facilities and participation opportunities (i.e.…”
Section: Program Capacity As a Mediatormentioning
confidence: 99%
“…However, recreational sport athletes demonstrate greater confidence to intervene when observing SV, which may reflect the priorities of their campus unit. Collegiate recreation departments are housed within the division of student affairs, where student development and diversity and inclusion are of primary concern (Lower-Hoppe et al, 2019). Within this environment, students may experience greater confidence to intervene on behalf of a peer.…”
Section: Student-level Predictors Of Sexual Violence Protective Factorsmentioning
confidence: 99%